PENGARUH PENGGUNAAN MEDIA DAKON BILANGAN TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN MATEMATIKA - Utami, Desy Wahyu; Hamdani, Hamdani; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to know the effect of use Dakon Number for the learning outcomes to student on mathematic class IV sdn 09 west pontianak. The form of this research was a quasy experimental design with non equivalent control group design. The population in this research is all students class IV SDN 09 west Pontianak. The sample of this research are IVA as experiment class and IVC as contol class. The sampling technique in this research use probability sampling (random). Data collection technique used measurement technique with essay test. The average learning outcomes of students in experiment class is 63,70, while the average learning outcomes of students in control class is 49,45. Based on the t-test with significance level  = 5% indicated there were differences between students that taught by using dakon number learning with students that taught without using dakon number learning. The value of effect size is 0,82 with moderate category is high. It means use dakon number give effect on student learning outcomes on mathematic class IV SDN 09 west pontianak. Keywords:  Dakon Number, Learning Outcomes, Mathematic